Malaysian English teachers’ perception on using songs in teaching English to young leaners - Chan, Russel Min Leong (2021)

(untitled)
This research presents the awareness of Malaysian English teacher towards the usage of songs to teach English to young learners and if they agree to use songs to teach English in the future. Reports have shown that Malaysia has an English proficiency level that is steadily dropping and this could be the effect of students losing interest and motivation to pick up the language as well as various psychological factors. This could be due to the learning materials being too boring and students being afraid to practice the language due to various factors. This study utilizes a quantitative research method via the survey questionnaires in the form of Google Forms. The findings from this research show that Malaysian primary school English teachers are aware of the benefits of songs in an English classroom and acknowledge them. It also shows that they are willing to use songs to teach various aspects of the English language. However, half of the participants in this study reports that they are would rather stick to the traditional teaching method to teach English. In order to produce students who not only score well in their examinations but also decent at using the English language on a daily basis, it is important for teachers to first realize the problem and make an effort in looking for creative solutions as well as implementing them in order to make learning and teaching interesting and enjoyable for both the learners and teachers alike.